Determinant of Capital Adequacy Ratio Using Intervening Variable Return on Assets - Luqman Hakim; Dewi Permata Sari; Budi Sutrisno (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the impact of inflation variables and the Loan to Deposit Ratio (LDR) on the Return On Assets (ROA) profitability ratio and the Capital Adequacy Ratio (CAR). This investigation is motivated by inconsistencies in previous studies compared to real-world observations, prompting a reevaluation by researchers. Employing a quantitative descriptive approach with multiple regression analysis for panel data, the research utilizes 9 cross-sectional samples over a 6-year time series. The research formula seeks to optimize CAR values through ROA as an intervening variable, focusing on banking sector companies listed on the Indonesia Stock Exchange. Two research models, subjected to selection tests (Chow Test, Hausman Test, and Lagrange Multiplier Test), were integrated. Findings from the first model reveal a negative correlation between inflation and ROA, aligning with established theory. The second model indicates that LDR significantly influences CAR with a negative correlation, consistent with theoretical expectations. Other variables fail to explain their impact on ROA in the first model and CAR in the second. These outcomes are anticipated to guide banking practitioners in Indonesia toward maximizing CAR.